Peranan budaya dan kepercayaan makan singkong masyarakat adat Cireundeu dalam menjaga kelestarian alam: Studi literatur - Nisa, Hana Khoirun; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Food holds significance beyond mere sustenance for certain communities; it encompasses beliefs, spirituality, and social bonds. The indigenous inhabitants of Cireundeu, a village steeped in tradition, uphold their distinctive culinary culture centered around cassava, a practice deeply intertwined with their beliefs. This study employs a literature review method, employing a bibliometric approach using PoP (Publish or Perish) for article retrieval and VoSviewer for analysis. The bibliometric analysis revealed that the article authored by Jabbaril titled